Avaliação da memória e exercício: a influência da prática de atividade física na memória visuomotora e visual de idosos em Canindé-Ceará - Fechine, Basílio Rommel Almeida (2012)
The objective of this study was to evaluate the visual-motor memory and visual memory of elderly people having as guiding parameters the non-practicing of physical activity, the practicing of unsystematic physical activity (without a professional accompaniment) and the practicing of systematized physical activity (with an orientation program and a professional supervision). We have worked with 260 elderly people of the age group 60. 90 years who lives in Canindé in Ceará state in 2011. With them, three groups were formed, the first is consisted of 100 individuals who are non- practitioners, the second with 100 individuals unsystematic practitioners and the third with 60 individuals non-practitioners of physical activity called experimental group who agreed to participate in a program of oriented physical activity and with professional supervision. The individuals in the experimental group participated in a program of physical activity from January to July 2011 with three weekly days. Before starting the intervention it was observed that the 100 individual who practice physical activity of the unsystematic group presented a statistically superior development for p<0,01 than the individuals of the other two groups in relation to the visual-motor memory and the visual memory. The same tests applied to the end of the experiment indicated that the individuals of the experimental group presented a significant superior development (p<0,01) in both tests of visual- motor memory and visual memory in relation to the initial application. The tests of visual memory applied to the end of the experiment in the three groups indicated that in relation to the first application, the group of the non-practitioners and unsystematic practitioners do not presented a statistically significant difference in relation to the initial application. In the other side, the difference in the development in these tests in relation to the final and initial application was statistically (p<0,01) superior in relation to the other two groups.